Regulation and government debt - Niclas Berggren; Christian Bjørnskov (Research Institute of Industrial Economics (IFN), 2018)
Government debt is high in most developed countries, and while it may reflect short-term attempts to kick-start the economy in times of crisis through fiscal stimulus, the longer-term consequences risk being detrimental to investment and growth. This makes it important to identify factors that are associated with debt. While previous studies have related government debt to economic and political variables, they have not incorporated the degree to which the economy is regulated. Using regulatory freedom (absence of detailed regulation of labor, business and credit) from the Economic Freedom of the World index, we conduct an empirical analysis covering up to 67 countries in the period 1975-2010. The main finding is that regulatory freedom, especially for credit, affects debt development negatively. The effect is more pronounced when the political system is fractionalized and characterized by strong veto institutions, indicating policy stability and credibility, and when governments have a right-wing ideology.
Keywords: E02; H63; 330; Debt; Economic freedom; Regulation; Markets; Stimulus; Keynesianism